The urgent need for Iran’s health system preparedness for war-related trauma amid geopolitical tensions - Esmaeil Fakharian; Mehrdad Mahdian (Archives of Trauma Research)
Editorial In light of the recent 12-day conflict (Israel and Iran) and escalating regional tensions, the necessity to re-evaluate the preparedness of Iran’s healthcare system for crisis and war has become a matter of national urgency. More than three decades have passed since the end of the Iran-Iraq war, and a new generation of physicians, nurses, technicians, and emergency responders now serves in healthcare facilities. Demographic analysis reveals that the majority of current healthcare workers in Iran, including general practitioners, residents, nurses, and emergency technicians, were born after 1991. Most of them have no direct experience in dealing with complex wartime trauma, mass casualty events, or military emergency protocols. Even at managerial levels, very few individuals have operational experience from the Iran-Iraq war. This generational gap, coupled with structural challenges in the healthcare system, poses a strategic threat to the nation’s ability to respond effectively in the event of a full-scale war or coordinated terrorist attacks. It is therefore imperative to enhance individual, systemic, and infrastructural readiness across medical education, hospital preparedness, and trauma research centers.Over the past decade, Iran’s health infrastructure has focused on chronic disease management, maternal and child health, and public epidemics like COVID-19. While these areas are essential, they have led to a significant neglect in preparing for special emergencies, including those related to war.Currently, very few hospitals in Iran possess dedicated military medicine departments or conduct regular drills for mass casualty incidents. Even in major trauma centers, crisis management protocols at hospital, interdepartmental, and city levels are not often updated, and joint field exercises with military, emergency, and relief organizations are rarely performed.[1,2] Trauma research centers affiliated with medical universities must take a leading role in promoting emergency preparedness. Their responsibilities include developing trauma protocols tailored to local conditions, organizing hands-on training programs for healthcare staff, conducting forward-looking studies based on realistic wartime scenarios, engaging in collaborative drills with military and disaster agencies, and applying lessons learned from international war-torn regions.[3-5] To strengthen national preparedness for wartime trauma, the following actions are essential:targeted re-training programs, use of simulators and realistic drills, establishment of rapid alert and command systems, development of national policies on military medicine, strategic stockpiling of essential supplies and trauma kits, and deployment of offline and virtual learning systems for medical personnel.[6]History repeatedly teaches us that preparedness during times of peace is essential for survival in times of crisis. Health systems cannot rely solely on institutional memory; rather, they must pursue structured, continuous, and scientific preparedness for trauma on a national scale. This is not only a professional imperative, it is a national duty.